DATA AND PROCESSING IN DEVELOPING ECCONOMIC APPLICATIONS - ADRIAN GHENCEA; OANA SIMONA HUDEA; DANA-FLORENTA SIMION (Challenges of the Knowledge Society)
Economic Informatics originates in the industry economy and the electronic processing of information. A clear distinction is made between IT and economic informatics, and further between general and particular economic informatics (the particular economic informatics meaning administration, industrial informatics etc). Economic informatics is deemed to be an applicative science relating to the conception, working modality and representation of IT and communication systems, oriented towards companies which are using electronic computers. This paper pursues to integrate applications allowing the information systems to interconnect at informational level, by information sharing, and at service level, considering the control of the related processes in real time.